Silicosis in Coimbatore district of Tamil Nadu: A passive surveillance study - Sivanmani, Keerthivasan (Medknow Publications & Media Pvt Ltd, 2013)
INTRODUCTION: Silicosis in Coimbatore district of Tamil Nadu: A passive surveillance study. AIM: This study was done to describe the level of preventive measures and level of awareness among the patients diagnosed with silicosis during a one-year period. SETTINGS AND DESIGN: Coimbatore Medical College Hospital. MATERIALS AND METHODS: This is a passive surveillance study based on patients diagnosed with silicosis in our outpatient facility for a one-year period between January 1, 2012 and December 31, 2012. RESULTS: Seventeen cases of silicosis were diagnosed based on history of exposure to silica and radiological features. The mean age was 55 years with 16 males and one female. The average duration of exposure was 22 years. A protective mask was used by 29% of the patients and one patient had awareness about the risks of exposure to silica. Active tuberculosis was found in 12% and old tuberculosis in 47% of patients; 59% of the patients were smokers. Spirometry showed a restrictive pattern in 59% of the patients. Radiologically nodular opacities with upper-zone predominance was found in majority of the cases. CONCLUSION: Most patients are exposed to silica in unorganized industries. Majority of the patients lack awareness about the disease and there is a low implementation of preventive and control measures. As this study was a passive surveillance, it represents only the tip of iceberg and an active field-level surveillance could reveal the true prevalence of this disease.